2018
DOI: 10.1111/jfbc.12689
|View full text |Cite
|
Sign up to set email alerts
|

Antiinflammatory and antioxidant activities of a polyphenol‐rich extract fromZizyphus lotusL fruit pulp play a protective role against obesity

Abstract: Zizyphus lotus (Zl) is used widely as a source of food and for the treatment of various ailments. Therefore, we investigated the biological activities of Zl against obesity and related disorders. Hence, male Wistar rats received either control diet, high fat diet (HFAD), or HFAD supplemented with the Zl pulp (HFADP) for 14 weeks. RAW 264.7 cells were used for the determination of antiinflammatory activities in vitro. It was observed that HFDP resulted in significantly reduced weight, blood sugar, and oxidative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 63 publications
(67 reference statements)
1
4
0
Order By: Relevance
“…2c). In addition, our data demonstrated that LPS-induced inflammation led to a significant increase in anti-inflammatory IL-10 gene expression, which is consistent with other studies (Salkowski et al, 1997;Sun, H. et al, 2017;Ghalem et al, 2018), and emphasizes the importance of IL10 immuno-regulatory function.…”
Section: Protein Hydrolysates Modulate the Expression Of Cytokines An...supporting
confidence: 92%
“…2c). In addition, our data demonstrated that LPS-induced inflammation led to a significant increase in anti-inflammatory IL-10 gene expression, which is consistent with other studies (Salkowski et al, 1997;Sun, H. et al, 2017;Ghalem et al, 2018), and emphasizes the importance of IL10 immuno-regulatory function.…”
Section: Protein Hydrolysates Modulate the Expression Of Cytokines An...supporting
confidence: 92%
“…Among these substances, polyphenols from jujube, secondary metabolites of plants, are important determinants of the nutritional and organoleptic qualities of Zizyphus lotus [21,22]. Several bioactive compounds extracted from jujubes have attracted the attention of many researchers due to their important biological actions, including antioxidant [19,23], enzyme inhibitory [24,25], antiproliferative and cytotoxic effects [24,26], anti-inflammatory, and other effects [27][28][29], which can be used in the food, pharmaceutical, and cosmetic industry.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors showed that Z. lotus has a significant antioxidant potential (Ghalem et al , 2018; Ghazghazi et al , 2014; Bakhtaoui et al , 2014; Bakchiche et al , 2013; Li et al , 2005). Rajinder et al (2015), tested the antiradical activity of the aqueous extract of the fruit of Ziziphus mauritiana and Eriobotrya japonica ,showed that the inhibition percentage for these two species were respectively 74.89 per cent and 51.07 per cent at a concentation of 200 mg/ml.…”
Section: Discussionmentioning
confidence: 99%